The biological and pharmacologic actions of Lawsonia inermis L - Amina Moutawalli; Fatima Zahra Benkhouili; Anass Doukkali; Hanane Benzeid; Ahmed Zahidi (Elsevier, 2023)
Background: Lawsonia inermis L., is a branched, glabrous shrub or small tree belonging to the Lythraceae family. A perennial plant commonly known as henna, it is native to North Africa and Southeast Asia. In this review, we highlighted previous information on the botanical description, and pharmacologic activities of Lawsonia inermis L. Methods: To collect the data on Lawsonia inermis L., we reviewed publications indexed in PubMed, Scopus, and Web of Science databases. The main judgment criterion was to mention ''Lawsonia inermis L.,'' or ''henna'' in the title, abstract or keywords, and the secondary judgment criterion was to mention ''pharmacological actions'', ''pharmacological activities,'' or ''pharmacological activity'' in the full text. Results: One hundred and eleven papers were identified after the initial database search from PubMed, Scopus, and the Web of Science. After abstract and title screening and deleting duplicates 84 articles were retained to be treated, and analyzed in this review. The information presented in this paper summarizes the phytochemicals and pharmacologic actions of Lawsonia inermis L., and their extracts. Conclusion: The reviewed articles approved different therapeutic powers and different biological actions of Lawsonia inermis L., in various in vitro and in vivo test models. Different parts of henna have been shown to have biological, pharmacological, and chemical activities, including Antibacterial, Antifungal, Antitumor and antiproliferative, Antiangiogenic, Larvicidal, Antileishmanial, Lousicide, Antimalarial, Hepatoprotective, Wound healing, Anti-inflammatory, Analgesic, Antipyretic, Memory enhancement, Enzyme inhibitor, and Antioxidant. This review provides direction for future studies on the composition and isolation of the active ingredients of Lawsonia inermis L., and references for the clinical use of prescriptions containing parts of this plant for the treatment of different diseases.